ANSIETAS DALAM NOVEL THIRTEEN REASONS WHY KARYA JAY ASHER - Pratiwi, Ade Eny; Tulung, Golda J.; Sigarlaki, Stephani J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThis Skripsi entitled â€œAnxiety in the Novel Thirteen Reasons Why by Jay Asherâ€ is intended to be one of the requirements to accomplish the â€œSarjanaâ€ at the Faculty of Humanities Manado. The objectives of this research are to identify and analyze the kind of â€žanxietyâ€Ÿ and the effect of â€žanxietyâ€Ÿ to the characters in the novel Thirteen Reasons Why by Jay Asher. The characterization of the characters, include the identification of â€žanxietyâ€Ÿ are described. In terms of methodology, the combination of two approaches applied namely the intrinsic as well as the extrinsic ones. The concept of â€žanxietyâ€Ÿ and its categories include the characters, are two concepts representing the extrinsic and the extrinsic ones. The psychological theory about anxiety by Freud in Minderop (2010) and supported theory by Davison, Neale and Kring (2012) and also paradigm by Roberts (1983) are used to be completed by a descriptive analysis. The results of this research show that the characters Clay Jensen, Hannah Baker and Mr. Potter tend to have anxiety. Clay Jensen categorized as objective anxiety and classified in phobia disorder, panic disorder and generalized anxiety disorder, Hannah Baker has objective anxiety and classified in panic disorder and post traumatic disorder, and Mr. Porter has objective anxiety. The effects are recklessness of the character Clay Jensen and depression of the character Hannah Baker and Mr. Porter. The depression of the character Hannah Baker causes the death as suicidal of the major characters Hannah Baker.Keywords: Literature, Anxiety, Psychologycal Analysis, Thirteen Reasons Why